2012
DOI: 10.12816/0002189
|View full text |Cite
|
Sign up to set email alerts
|

Youths and Career Development in Nigeria : Problems and Prospects

Abstract: This paper is a broad overview of youths and career development in Nigeria. In discussing the sub-topics therein, Nigeria peculiarities were taken into consideration. The discourse captured salient areas like youth upbringing, strategies for crime and juvenile delinquency control, youth gangs, youth education, youth unemployment among others were identified as problem areas among Nigerian youths. The paper argues that a critical evaluation of Nigerian educational system is needed to ensure that graduates do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…This implies that the participation of farmers in ASTC project has brought a sign finding is line with that of Chukwuemeka (2012) that observed that most assisted programmes by the government helped in promoting small-scale autonomous enterprise, increased production, and marketing and training in the project. …”
Section: Impact Of Astc On the Output Of Participant And Non-participantsupporting
confidence: 80%
“…This implies that the participation of farmers in ASTC project has brought a sign finding is line with that of Chukwuemeka (2012) that observed that most assisted programmes by the government helped in promoting small-scale autonomous enterprise, increased production, and marketing and training in the project. …”
Section: Impact Of Astc On the Output Of Participant And Non-participantsupporting
confidence: 80%
“…Several years after, Nigeria still flounders in its attempt to achieve the objectives of the Millennium Development Goals and adequately address the problems and aspiration of the Nigerian youth (Bamidele et al, 2013;African Forum and Network on Debt and Development (AFRODAD), 2005). In addition to poor value orientation, the Nigerian youth continues to be plagued by the challenges of high rate of youth unemployment, youth neglect, social vices, poverty, negativism, inadequacy and ultimately, deviance and crime (Chukwuemeka et al, 2012). This paper aims to investigate the extent to which Nigeria has been able to achieve the lofty objectives of the Millennium Development Goals (MDGs) and the extent to which it has improved the development of its teeming and talented youth.…”
mentioning
confidence: 99%